Effects of Various Energy Suppliers in Green Processes for Obtaining Silver Nanoparticles. Issue 1 (1st December 2020) - Pulit-Prociak, Jolanta; Staroń, Paweł; Staroń, Anita; Chwastowski, Jarosław; Banach, Marcin
Abstract: The productions of stable suspensions of silver nanoparticles using a microwave reactor, an ultraviolet (UV) reactor, a low‐frequency low‐temperature plasma reactor, a high‐pressure reactor, and an open reactor are compared. All reactors served as sources of energy for stimulating the nanoparticle growth process. The silver nanoparticles were obtained based on the chemical reduction method. The processes were conducted using gallic acid as the reducing‐stabilizing substance. The influence of the variable parameters time (for all types of reactors), temperature (for the open and high‐pressure reactors), power (for the microwave reactor), energy density (for the UV reactor), and voltage (for the low‐frequency low‐temperature plasma reactor) was investigated. Temperature was found to be the most important factor influencing all processes. Abstract : Suspensions of silver nanoparticles with a fixed concentration were produced using five different types of reactors as energy sources and gallic acid as a reducing‐stabilizing agent. Temperature was the most important factor influencing all processes. It directly affects the activity of gallic acid in silver nanoparticle formation and determines the size and shape of the nanoparticles.